Pelatihan Pengelasan SMAW Bagi Warga Muda di Desa Silinda, Serdang Bedagai, Sumatera Utara - Pasaribu, Muhamamd Nuh Hudawi; Eswanto, Eswanto; Januariyansah, Sapitri; Iswandi, Iswandi; Siahaan, Muhammad Yusuf Rahmansyah (IRA Jurnal Pengabdian Kepada Masyarakat (IRAJPKM), 2025)
Young residents of Silinda Village are very interested in skills to open up entrepreneurial job opportunities because, in general, residents only have farming skills. To realize this interest and create entrepreneurial work, community service was held in the form of SMAW welding training. This SMAW welding training was chosen because the price of equipment and materials is easy to obtain and economical so that it can be realized immediately. The skills training provided is carried out by explaining theoretical material and welding practice. The theoretical material is in the form of safety before welding, safety during welding, safety after welding is complete, and the function of the tools and materials needed, while the practical welding material is in the form of measurement techniques, how to cut materials, and how to connect iron using the SMAW method. The results obtained from the SMAW welding skills training are the creation of 1 door and 4 tables. With the results of the skills that have been possessed, young residents are confident in opening a business to increase income.